On an Inflated Unit-Lindley Distribution (Journal of Statistical Research, 2022)
Modeling fractional data in various real-life scenarios is a challenging task. This paper considers situations where fractional data are observed in the interval [0,1]. The unit- Lindley distribution has been discussed in the literature where its support lies between 0 and 1. In this paper, we focus on an inflated variant of the unit-Lindley distribution, where the inflation occurs at both 0 and 1. Various properties of the inflated unit-Lindley distribution are discussed and examined, including point estimation based on the maximum likelihood method and interval estimation. Finally, extensive Monte Carlo simulation and real-data analyses are carried out to compare the fit of our proposed distribution along with some of the existing ones such as the inflated beta and the inflated Kumaraswamy distributions.Journal of Statistical Research 2021, Vol. 55, No. 2, pp. 299-311